Hyperosmolar Hyperglycemic State (HHS) - Gusti Bagus Widiamatra Linggabudi, I; Salsabilla, Rani; Aulia Fitroningtyas, Elvika (Jurnal Syntax Fusion, 2022)
Hyperosmolar hyperglycemic syndrome (HHS) is a clinical condition arising from complications of diabetes mellitus. This clinical condition was previously called a non-ketotic hyperglycemic coma; non-ketotic hyperosmolar hyperglycemic syndrome, and non-ketotic hyperosmolar coma (KHONK). Current HHS diagnostic criteria include plasma glucose levels >600 mg/dL and an increase in effective plasma osmolality >320 mOsm/kg in the absence of ketoacidosis. Hyperosmolar hyperglycemic syndrome (HHS) usually occurs with lower insulinopenia levels compared to diabetic ketoacidosis (DKA), but its pathophysiology is considered the same. The mortality rate in Hyperosmolar hyperglycemic syndrome (HHS) can be up to 20% which is about 10 times higher than the death seen in diabetic ketoacidosis. Clinical outcomes and prognosis in HHS are determined by several factors: age, degree of dehydration, and the absence or absence of other accompanying diseases.